Answer:
(f + g)(x) = x^2 + 3x - 6
Step-by-step explanation:
Given f(x) = x^2 + x − 2 and g(x) = 2x − 4
Plug in:
(f + g)(x) = x^2 + x − 2 + 2x − 4
(f + g)(x) = x^2 + 3x - 6
Let the angles be A and C
<span>Complimentary angles, therefor </span>
<span>A + C = 90 </span>
<span>The measurement of the complement of an angle exceeds the measure of the angle by 25% (you used a % sign so I'll use % instead of degrees) </span>
<span>C = 1.25A </span>
<span>Substitute </span>
<span>A + 1.25A = 90 </span>
<span>2.25A = 90 </span>
<span>A = 40º <----- </span>
<span>C = 50º <----- </span>
<span>------------------------------ </span>
<span>If you meant 25º </span>
<span>A + (A + 25) = 90 </span>
<span>2A + 25 = 90 </span>
<span>2A = 65 </span>
<span>A = 32.5º </span>
<span>C = 57.5º</span>